Pesticides Use Patterns in Litchi (Litchi chinensis sonn.) Orchards at Ishwardi, Pabna, Bangladesh - Azad, M A K (Journal of Environmental Science and Natural Resources, 2025)
Ishwardi Upazilla, Pabna is known as the capital of litchi in Bangladesh. Litchi is suffered from various kinds of insect infestations, diseases and natural calamities. This study was conducted on the growers of litchi at Ishwardi Pabna to identify the pesticides use pattern in litchi orchards. A structured questionnaire survey was carried out to collect the data among the litchi growers. The litchi grower expressed that fruit borer (Conopomorpha sinensis) attacks of litchi releases unpleasant odor and drastically lowers its market value. The major constraints of litchi cultivation are burning of litchi skin due to heat waves, unseasonal rain in the months of April-May and drought. Other constraints are mite and litchi leaf rollers infestation. The litchi growers used more than 15 types of pesticides during pre-flowering, flowering, litchi developing and harvesting periods against insect pests. Out of these pesticides, Cypermethrin was the top use insecticides. The litchi growers also used Profenophose, Difenoconazole, Azoxystrobin + Difenoconazole, and Thiamethoxam+ Chlorantraniliprole in litchi orchards. All of these pesticides are harmful to human health and environment. Environ. Sci. & Natural Resources, 14(1&2): 27-30, 2025